2007
DOI: 10.1089/aid.2006.0244
|View full text |Cite
|
Sign up to set email alerts
|

Value of the HLA-B*5701 Allele to Predict Abacavir Hypersensitivity in Spaniards

Abstract: The use of abacavir (ABC) may be associated with a hypersensitivity reaction (HSR) that requires discontinuation of the drug. The HLA-B*5701 allele has been linked to this HSR. Information on the strength of this association across distinct geographic regions and ethnicities is scarce. We tested HLA-B*5701 in 53 Spaniards infected with HIV who received ABC treatment. The presence of HLA-B5701 had strong positive and negative predictive values for ABC HSR, 92% and 63%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 9 publications
(8 reference statements)
1
19
0
1
Order By: Relevance
“…The drug manufacturer, Glaxo Smith Kline, carried out a prospective study and several retrospective studies and showed a strong association between HLA-B*5701 and abacavir-induced hypersensitivity reaction (11). Similar findings were also reported by many other groups (12)(13)(14). Recently, the abacavir label was updated to reflect the new findings, and genotyping HLA-B*5701 was recommended before prescribing abacavir.…”
Section: Drug Efficacy/safety and Biomarkerssupporting
confidence: 59%
“…The drug manufacturer, Glaxo Smith Kline, carried out a prospective study and several retrospective studies and showed a strong association between HLA-B*5701 and abacavir-induced hypersensitivity reaction (11). Similar findings were also reported by many other groups (12)(13)(14). Recently, the abacavir label was updated to reflect the new findings, and genotyping HLA-B*5701 was recommended before prescribing abacavir.…”
Section: Drug Efficacy/safety and Biomarkerssupporting
confidence: 59%
“…Abacavir hypersensitivity was diagnosed on the basis of only clinical criteria in 9 studies [5][6][7][8][10][11][12]14,15 and clinically and immunologically (at least in some participants) in 4 studies. 3,4,9,13 All studies except 1, in which no participants carried the HLA-B*57:01 allele, 14 found a significant association between HLA-B*57:01 expression and abacavir hypersensitivity.…”
Section: To the Editormentioning
confidence: 99%
“…The patch testing was first applied by GSK researchers in the study of abacavir-induced HSR [3], and has been widely adopted to identify abacavir-induced HSR. Several studies have shown that patch testing significantly reduced false diagnosis of abacavir-induced HSR [21,47,51,52] and strengthened the genotype-phenotype association. By combining with patch testing, HLAB*57:01 screening had 100% sensitivity to predict abacavir-induced HSR regardless of race, indicating that such screening could be valuable to prevent abacavir-induced HSR even in populations with low prevalence of HLA-B*57:01 [31,53].…”
Section: Role and Benefit Of Hla-b*57:01 Screeningmentioning
confidence: 99%